ECHO-UAN project seeks to bring knowledge closer to the general public (VITAL, 2025)
Project ECHO connects specialists to share knowledge. Since 2003, it has benefited millions of patients. At UAN, active aging topics were promoted, led by Dr. Cindy Paola Agudelo.
Keywords: Tele-mentoring; Conferences; Aging